Synthesis and Characterization of N,N-Dimethylamino- N',N"-diarylamino Phosphine Oxides - NAGHIPOUR, ALI; ABBASI, S. (Asian Journal of Chemistry, 2010)
Synthesis and characterization of some novel N,N-dimethyl-N',N''-diaryl-phosphoramides, Me2NP(O)(NHAr)2 (where Ar = phenyl, 2-methylphenyl, 3-methyl-phenyl and 4-methylphenyl, compounds 1-4, respectively), may act as insecticides or have other useful biological activities are reported. These compounds were prepared by the reaction of N,N-dimethylphosphoramido dichloride and the appropriate amines. They strength of aromatic amines and the effects of aromatic amines on the P-NMe2 bond are explained and a reasonable correlation between 31P chemical shifts and (P=O) vibration frequencies is identified.